2018
DOI: 10.1016/j.ejrad.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation provided by dental radiological procedures in a pediatric population

Abstract: The CBCT doses and radiation risk vary but remain in the lower levels of the relative risk of medical exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 23 publications
0
29
0
3
Order By: Relevance
“…8 A recent survey of pediatric dentists reported that only 22% used rectangular collimation. 9 Previous work on dental radiography risk estimates has described risk in terms of fatal cancer cases per 1 million radiographic examinations, 10 per 100,000 examinations, 11 and even 3 per 18,200 examinations. 12 However, no recent paper has presented a projection for the total number of possible cancer cases resulting from all dental offices or by specialty in the United States.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
“…8 A recent survey of pediatric dentists reported that only 22% used rectangular collimation. 9 Previous work on dental radiography risk estimates has described risk in terms of fatal cancer cases per 1 million radiographic examinations, 10 per 100,000 examinations, 11 and even 3 per 18,200 examinations. 12 However, no recent paper has presented a projection for the total number of possible cancer cases resulting from all dental offices or by specialty in the United States.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
“…En relación con el uso de EP en pacientes pediátricos, no existe suficiente evidencia que permita determinar dosis de radiación en estos grupos poblacionales, cuyos tejidos son altamente sensibles a la radiación ionizante (25). Por esto, bajo el principio ALADAIP (del inglés as low as diagnostically aceptable being indication-oriented and patient-specific), establecido por el proyecto DIMITRA (del inglés dentomaxillofacial paediatric imaging: an investigation towards low-dose radiation induced risk), no se recomienda el uso del EP en este grupo de pacientes hasta conocer el riesgo asociado a su uso (26).…”
Section: Seguridad Para El Pacienteunclassified
“…(1) Los pacientes pediátricos tienen mayor riesgo de inducción de cáncer por radiación ionizante que los pacientes adultos. (17) Esto se debe a que sus órganos en desarrollo son más radiosensibles y a su mayor expectativa de vida, siendo las niñas significativamente más radiosensibles que los niños. (17) Modelo lineal sin uMbRal Existen distintos modelos que explican la relación entre las bajas dosis de radiación ionizante y sus efectos adversos.…”
Section: Efectos De Las Radiaciones Ionizantesunclassified
“…(17) Esto se debe a que sus órganos en desarrollo son más radiosensibles y a su mayor expectativa de vida, siendo las niñas significativamente más radiosensibles que los niños. (17) Modelo lineal sin uMbRal Existen distintos modelos que explican la relación entre las bajas dosis de radiación ionizante y sus efectos adversos. (18) La Comisión Internacional de Protección Radiológica (ICRP del inglés International Commission on Radiological Protection) avala el modelo lineal sin umbral (LNT del inglés linear-no-threshold).…”
Section: Efectos De Las Radiaciones Ionizantesunclassified